Relationships among Pratylenchus jaehni and P. coffeae populations from Brazil. - Wilcken, Silvia Renata Siciliano; Mori, Edson Seizo [UNESP]; Bacci, Maurício [UNESP]; Ferraz, Luiz Carlos C.B.; Oliveira, Claudio Marcelo G.; Inomoto, Mario M. (My University, 2008)
Wilcken, S.R.S., E.S. Mori, M. Bacci, L.C.C.B. Ferraz, C.M.G. Oliveira & M.M. Inomoto. 2008. Relationships among Pratylenchus jaehni and P. coffeae populations from Brazil. The relationships among Pratylenchus jaehni (C) and six amphimitic Pratylenchus populations from Brazil (three from banana, PcB1, PcB2, and PcB3; one from Aglaonema sp., M2; one from coffee, K5; and one from citrus, C) were studied through morphological and molecular analysis, and pathogenicity test. The analysis of morphometric characteristics of PcB1, M2, C2 and K5, compared with P. jaehni and P. coffeae (K6) data obtained from literature, delineated three groups: P. coffeae (K6), PcB1 and M2; P. jaehni (C1) and C2; and K5. RAPD analysis of PcB1, PcB2, PcB3, M2, C2, K5 and P.jaehni (C1) demonstrated that these populations form three distinct genetic groups: PcB1, PcB2, PcB3 and M2; P.jaehni and C2; and K5. In pathogenicity test, K5 reproduced well on coffee and caused extensive root necrosis, but C2 did not. Population C2 reproduced well on Rangpur lime, which was previously rated as poor host to K5. Therefore, the results demonstrated that C2 is P. jaehni, K5 is an undescribed species of Pratylenchus, and PcB1, PcB2 and PcB3 are P. coffeae. The taxonomic status of M2 remains inconclusive.